2016
DOI: 10.1109/jstqe.2015.2501382
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Chaotic Fiber-Based Nonlinear Polarization Scrambler

Abstract: International audienceWe report a simple and efficient all-optical polarization scrambler based on the nonlinear interaction in an optical fiber between a signal beam and its backward replica which is generated and amplified by a reflective loop. When the amplification factor exceeds a certain threshold, the system exhibits a chaotic regime in which the evolution of the output polarization state of the signal becomes temporally chaotic and scrambled all over the surface of the Poincaré sphere. We numerically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In this section we discuss the third regime of operation of the Omnipolarizer, which allows implementing an all-optical fully chaotic polarization scrambler. Indeed, as underlined in Sections II and III, for a large power imbalance between the forward beam and its backward replica, the system exhibits a genuine chaotic dynamics so that even a well-polarized incident signal becomes scrambled all over the Poincaré sphere at the fiber output [64][65][66][67][68][69].…”
Section: All-optical Chaotic Polarization Scramblermentioning
confidence: 98%
See 3 more Smart Citations
“…In this section we discuss the third regime of operation of the Omnipolarizer, which allows implementing an all-optical fully chaotic polarization scrambler. Indeed, as underlined in Sections II and III, for a large power imbalance between the forward beam and its backward replica, the system exhibits a genuine chaotic dynamics so that even a well-polarized incident signal becomes scrambled all over the Poincaré sphere at the fiber output [64][65][66][67][68][69].…”
Section: All-optical Chaotic Polarization Scramblermentioning
confidence: 98%
“…Two threshold values of the reflection coefficient ρ are found that characterize this chaotic dynamics, which are ρA=9π / (16•L•Ps,out•) and ρC≃5ρA, being Ps,out the power of the forward signal at the fiber exit. If ρ is below the threshold ρA then the system exhibits stationary states that are stable, therefore a signal which is fully polarized in input (DOP=1) turns out to be still polarized in output with an SOP that strictly depend on the system parameters and on the input SOP [69]. On the other hand when ρ>ρC the stationary states don't exhibit anymore a monotonic evolution along the fiber length and thus, start to oscillate and become unstable.…”
Section: All-optical Chaotic Polarization Scramblermentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, for larger reflection coefficients, i.e., ρ >>1, a chaotic dynamics can be reached, leading to an all-optical scrambling of the output polarization [70], which is briefly introduced in next section and discussed in more details elsewhere [71].…”
Section: Principle Of Operationmentioning
confidence: 99%